Class Collective Efficacy and Class Size as Moderators of the Relationship between Junior Middle School Students’ Externalizing Behavior and Academic Engagement: A Multilevel Study - Tian, Yu; Bian, Yulong; Han, Piguo; Gao, Fengqiang; Wang, Peng (Frontiers in Psychology, 2017)
This study examined the relationship between externalizing behavior and academic engagement, and tested the possibility of class collective efficacy and class size moderating this relationship. Data were collected from 28 Chinese classrooms (N = 1034 students; grades 7, 8, and 9) with student reports. Hierarchical linear modeling (HLM) was used to test all hypotheses and results revealed a negative relationship between externalizing behavior and academic engagement; class collective efficacy was also significantly related to academic engagement. Additionally, class collective efficacy and class size moderated the relationship between externalizing behavior and academic engagement: For students in a class with high collective efficacy or small size (≤30 students), the relationship between externalizing behavior and academic engagement was weaker than for those in a class with low collective efficacy or large size (≥43 students). Results are discussed considering self-regulatory mechanisms and social environment theory, with possible implications for teachers of students’ learning provided.